Carbapenem-Resistant Enterobacteriaceae Bloodstream Infection Treated Successfully With High-Dose Meropenem in a Preterm Neonate - Yue-E Wu; Hai-Yan Xu; Hai-Yan Shi; John van den Anker; John van den Anker; John van den Anker; Xiao-Yu Chen; Wei Zhao; Wei Zhao (Frontiers Media S.A., 2020)
Carbapenem-resistant enterobacteriaceae (CRE) bloodstream infections have been rapidly spreading worldwide with a high mortality and pose a challenge to therapeutic decision-making, especially in premature neonates because insufficient empirical antimicrobial therapy is independently associated with high mortality. This case reported that a premature infant with CRE bloodstream infection was treated successfully with high-dose meropenem treatment with model-based therapeutic drug monitoring (TDM). In clinical settings, treatment target attainment of meropenem can be improved by increasing the frequency of administration, prolonging the infusion time, and using a high dose. This case report shows a successful regimen for CRE infection in a premature neonate and emphasizes the utility of model-based TDM of high-dose meropenem treatment. The adequate antimicrobial benefit provided by innovative techniques could ensure the efficacy and safety of high-dose meropenem therapy for CRE infection.